“Wait, How Do I Say that in English?” Communication Strategies for English as a Foreign Language Learners - Zulfadli Aziz; Ika Apriani Fata; Syarifah Balqis (Lingua Cultura, 2018)
This research aimed to investigate communication speaking skill strategies applied by two groups of English foreign language learners in two boarding senior high schools in Aceh, Indonesia. Of the successful group, there were 52 learners and of the less successful group 24 learners. To collect the data, this study employed the observation sheet adapted by Tarone(1978), which determined nine categories of communication strategies; approximation, word coinage, circumlocution, literal translation, language switch, mime, appeal for assistance, topic avoidance, and message abandonment. The students were observed during their speaking class. The result of this research is the literal translation, approximation, and language switchbecome the most frequent strategies used by the less successful learners. It implies that the students have had difficulties communicating in the target language. On the other hand, successful learners prefer to use approximation, literal translation, and appeal for assistance strategies. It implies that the students tend to speak and communicate well, if not yet fluently. Based on the findings, it is suggested that English teachers should introduce several communication strategies for both groups of learners to improve their effective communication.